Broiler Production Goals - Important Numbers - Gary D. Butcher; Amir H. Nilipour (EDIS)
Producing a profitable broiler requires that certain standards be met, some even before the chicks are placed on the farm and during the grow-out. The most important principle is to set the best quality fertile eggs in the machines and ensure that all eggs have been handled properly. It is preferred not to hold the eggs more than three days and the egg room must have the right temperature and humidity during storage to avoid killing or weakening the blastoderm. The longer the eggs are kept in storage the poorer the chick vigor, quality and hatch. This document is VM134, one of a series of the Veterinary Medicine-Large Animal Clinical Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date May 16, 2005.